In Silico Models for Drug Discovery - Kortagere, Sandhya; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Infectious diseases caused by viruses, parasites, bacteria, and fungi are the number one cause of death worldwide. Although new technologies have improved diagnosis of infectious diseases, the efficacy of all known current anti-infective agents is threatened by the spread of drug-resistant forms of the pathogens. Hence, there remains an urgent need to develop anti-infective agents that target drug-resistant pathogens. In Silico Models for Drug Discovery presents a comprehensive look at the role in silico models play in understanding infectious diseases and in developing novel therapeutics to treat them. Written by leading experts in the field, chapters cover topics such as techniques to derive novel antimicrobial targets, methods of interpreting polypharmacology-based drug target networks, and molecular dynamics techniques used to compute binding energies of drugs to their target proteins, to name a few. Written in the successful Methods in Molecular Biology™ series or in review article format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and easily accessible, In Silico Models for Drug Discovery seeks to serve both professionals and novices involved in the study and treatment of infectious diseases.
Virtual Screening in Drug Design -- In Silico Systems Biology Approaches for the Identification of Antimicrobial Targets -- Genome Comparisons as a Tool for Antimicrobial Target Discovery -- In Silico Models for Drug Resistance -- An In Silico Model for Interpreting Polypharmacological Relationships in Drug-Target Networks -- On Exploring Structure–Activity Relationships -- Molecular Dynamics Simulations in Drug Design -- Databases and In Silico Tools for Vaccine Design -- In Silico Models for B-Cell Epitope Recognition and Signaling -- The Collaborative Drug Discovery (CDD) Database -- Recognition of Nontrivial Remote Homology Relationships Involving Proteins of Helicobacter pylori: Implications for Function Recognition -- Identification of Novel Anthrax Toxin Countermeasures Using In Silico Methods -- Rational Design of HIV-1 Entry Inhibitors -- Malarial Kinases: Novel Targets for In Silico Approaches to Drug Discovery -- Designing Novel Inhibitors of Trypanosoma brucei -- Computational Models for Tuberculosis Drug Discovery.
Keywords: Pharmacology; Medicinal chemistry; Pharmacology/Toxicology.; Medicinal Chemistry